The culture of the school in the reduction of quilombolas roots / A cultura da escola no resgate das raízes quilombolas - Cristina Simone de Sena Teixeira; Maria do Socorro Silva de Aragão; Sanádia Gama dos Santos (Universidade Estadual de Alagoas, 2019)
The aim of this article is to sensitize educators, education managers, students, family members and the school community about the importance and necessity of promoting racial equality, provoking reflections on ethnic-racial issues, African cultural contribution, strengthening of identity and quilombola self-esteem in the remnant communities of the municipality of Traipu - Alagoas, starting with a special look at the role of education in dealing with these issues, in light of Federal Law 11.645, of March 10, 2008, which provides for the mandatory inclusion of programmatic content on History Africa and Afro-Brazilian Culture in school curricula, as well as the adoption of educational policies and pedagogical strategies for valuing ethnic-cultural diversity. It is also intended to overcome the negative view of the African and its descendants, built by the racists in Brazil, thus stimulating a change of mentality of those who insist on disregarding that black influence has enriched Brazilian culture and must be recognized